PENERAPAN MEDIA KARTU BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIAH ANAK USIA DINI - Povi Yulmi Putri; Hulailah Istiqlaliyah (Fakultas Tarbiyah IIQ Jakarta, 2024)
The aim of this research is to describe the application of card media in improving the ability to read Hijaiah letters in children aged 4-5 years at Yasmin Jatikramat Bekasi Kindergarten. This research uses descriptive qualitative research. Data collection methods were carried out by means of observation, interviews and documentation. The data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of the research show that the application of card media in improving the ability to read Hijaiah letters in children aged 4-5 years at Yasmin Jatikramat Bekasi Kindergarten is running effectively as evidenced by children being more enthusiastic and enthusiastic in learning and achieving graduate targets, the results of routine evaluations held, as well as achievements achieved by students at Kindergarten Yasmin Jatikramat Bekasi.